Frequency of pes anserine bursitis in patients with knee osteoarthritis - Mohammadi-Kebar, Yousef; Azami, Ahad; Rezaei-Bana, Shima (International Journal of Research in Medical Sciences, 2023)
Background: Knee pain is a very common disease in the elderly, which is often attributed to osteoarthritis but pes anserine bursitis also can cause knee pain, especially in OA patients. The aim of this study was to determine the frequency of pes anserine bursitis in patients with knee osteoarthritis. Methods: This cross-sectional descriptive study included 245 patients with definitive knee osteoarthritis referred to Imam Khomeini Hospital in Ardabil city from September 2020 to December 2021. All patients were sent to ultrasonography to diagnosis Pes Anserine Bursitis. Osteoarthritis was divided into 4 groups based on the radiographic classification of Kellgren-Lawrence. The severity of knee pain was also determined by the Visual Analogue Scale (VAS). The necessary data were collected by a checklist and then analysed by statistical methods in SPSS version 22. Results: Total 175 out of 245 patients (71%) were diagnosed with pes anserin bursitis. There was a significant relationship between age, gender, BMI, OA and staging of OA with the risk of anserin bursitis. Conclusions: Results showed that the high prevalence of anserine bursitis in patients studied indicates the importance of this issue and the need for attention by physician as one of knee pain reasons. Since the clinical examination has a significant diagnostic power in the detection of anserin bursitis, it is recommended that special attention be paid to the clinical examination. Attention to the risk factors in the country such as obesity, the use of toilets and so on, which can be controlled and can be prevented.